Study of Zinc Deposited in the Presence of Organic Additives for Zinc-based Secondary Batteries - Chladil, Ladislav; Čech, Ondřej; Smejkal, Jan; Vanýsek, Petr (Elsevier, 2018)
This work is focused on the effect of selected organic additives on zinc deposit properties in relation to a possible utilizing the additives for a zinc based battery systems worked with alkaline electrolyte. The Zn layers were deposited on tin substrate from the KOH based electrolytes saturated by zinc oxide and with addition of different organic surfactants - CTAB, Slovasol 2520/2, Tween 20 and Lugalvan G 35 in concentration 500ppm. Depositions were held under low current densities 10mA/cm2 where the mossy porous deposit grows from pure KOH solutions. All additives were examined with emphasis on the study of zinc deposit morphology and their ability to create uniformly distributed porous structure which could exhibit fast electrode kinetic. All deposits were studied by X-ray crystallography and preferred structure orientations are reported. For the purpose of using additives directly in the battery systems we evaluated also the corrosion properties of the KOH solution with addition of the above mentioned surfactants. It has been found that the presence of CTAB and Slovasol 2520/2 lead to a pyramidal texture, Lugalvan G 35 produced micro-crystalline deposit with opened porous structure and finally presence of Tween 20 lead to nano-crystalline highly porous deposit almost without preferred orientation.

This work is focused on the effect of selected organic additives on zinc deposit properties in relation to a possible utilizing the additives for a zinc based battery systems worked with alkaline electrolyte. The Zn layers were deposited on tin substrate from the KOH based electrolytes saturated by zinc oxide and with addition of different organic surfactants - CTAB, Slovasol 2520/2, Tween 20 and Lugalvan G 35 in concentration 500ppm. Depositions were held under low current densities 10mA/cm2 where the mossy porous deposit grows from pure KOH solutions. All additives were examined with emphasis on the study of zinc deposit morphology and their ability to create uniformly distributed porous structure which could exhibit fast electrode kinetic. All deposits were studied by X-ray crystallography and preferred structure orientations are reported. For the purpose of using additives directly in the battery systems we evaluated also the corrosion properties of the KOH solution with addition of the above mentioned surfactants. It has been found that the presence of CTAB and Slovasol 2520/2 lead to a pyramidal texture, Lugalvan G 35 produced micro-crystalline deposit with opened porous structure and finally presence of Tween 20 lead to nano-crystalline highly porous deposit almost without preferred orientation.
Study of Zinc Deposited in the Presence of Organic Additives for Zinc-based Secondary Batteries
Keywords: Zinc deposition; additive; electrodeposition; corrosion; Zinc deposition; additive; electrodeposition; corrosion